Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Pegawai dengan Employee Engagement dan Komitmen Organisasional Sebagai Variabel Intervening - Marwan Marwan; Fadhliah M. Alhadar fadhliah; Adfil Alsa adfil (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
One factor main in increase performance employee is through leadership transformational. Study this aim for knowing influence leadership transformational to performance mediated employee with employee engagement and commitment organizational. Study this is study quantitative with technique data collection in the form of share questionnaire to whole employee Service Communication Central Halmahera Regency, totaling 75 people used as respondents. Technique analysis used in study this is analysis Partial Least Square (PLS) with help SmartPLS version 3.2. Results research conducted show that leadership transformational no take effect by direct to performance employee however required mediation employee engagement and commitment organizational. Very recommended in study next for expand study on organization government that owns Duty and function management income original area. Also recommended in study next notice other variables like compensation and competence in increase performance employee.